CHRISTIAN SPIRITUAL PERSPECTIVE IN HELPING PROFESSIONS (Religious dialogue and cooperation, 2021)
Intervention in helping professions involves a lot morethan knowledge-based methods and skills adopted by professionals,often it involves exchange of ideas, feelings, beliefs, and values thatmay or may not be directly addressed or acknowledged, but haveprofound influence in the process of recovery or reestablishmentof the wellbeing of clients. We will try to prove the link betweenChristianity and contemporary society values such as individualfreedom, right to service (human right), social justice, humandignity, professional integrity, and subsidiarity.Christian spiritual perspective accepts the belief that God existsand that He created the entire universe, including the materialand spiritual realms. These spheres are in mutual coexistence,reflecting intelligent creation, and exist in reality independent ofhumanity. In the created order, humans are ontologically unique,created in the image of God. Common to all people is their dignity,value, personality, creativity, strengths, and rationality. The valueof human differences and autonomy is an important ideal that isemphasized in Christian spiritual perspective in understandinghuman uniqueness and individuality.Christian spiritual perspective will be therefore seen as a resourcethat promotes client efforts to solve or deal with problems. TheChristian spiritual perspective can be used as part of therapeuticapproaches in counseling models based on empowering strengthsand recognizing the role of life events in the therapy, an interactiveprocess in which individuals construct their meaning on the basis oflife experiences.
Keywords: Christianity; spirituality; individual freedom; human rights; social justice; human dignity; subsidiarity; professional integrity